The Concept Of Alonto On Policy Integration Of The Philippine Goernment: A Critical Analysis - Mohammad Nashief S. Disomimba; Kalsom Ali (Centre for Enhancing Knowledge (CEK), UK (Website, 2024)
Non-Indexed Publication